Use of red cell indices in the diagnosis of beta-thalassemia trait - Shanker, Swathy; Murthy B., Niranjana; Koul, Aakanksha (International Journal of Research in Medical Sciences, 2026)
Background: Hemoglobinopathies are found to be the most common monogenic hereditary disorders. The haematological features of thalassemia trait are similar to that of microcytic hypochromic anemia and differentiation is mainly based on High Performance Liquid Chromatography (HPLC) results. Simple blood count indices have been developed for prediction of possible presence of thalassemia trait. This study aimed to assess the diagnostic role of red cell indices in reporting beta-thalassemia trait. Methods: A total of 124 patients were included in this study. All cases of microcytic hypochromic anemia were included in the study and were classified as positive or negative for beta-thalassemia trait based on the indices analysed. Cases were sent for high performance liquid chromatography for confirmation and statistical analysis was carried out to find the index that best suited the study population. Results: There was a slight male predominance in the study population. Shine and Lal index showed the highest sensitivity of 100%, followed by Red Cell Distribution Width Index (RDWI) and Kandhro index (98.9%). Sirdah index showed the highest specificity of 71.4% followed by Zaghloul 1 index showing specificity of 67.8%. The low specificity in this study could be attributed to the fact that only a few cases that were flagged negative by the CBC indices were selected. Conclusions: The accuracy of each index in predicting the presence of beta-thalassemia trait varies from population to population. Population based studies are warranted to assess the indices that are most accurate ,and thereafter these indices must be included in routine hematology investigations to aid in early detection of beta thalassemia trait.